Vaga-lumes bioindicadores de poluição luminosa e riqueza de espécies em áreas naturais da Serra de Paranapiacaba e em áreas urbanizadas - Santos, Raphael Machado (2013)
Bioluminescent beetles are common for their wide distribution in the world, but the composition of the fauna of these organisms is still unknown to most of the areas where they occur. Brazil is the country with the largest number of cataloged species of bioluminescent insects, but studies of faunal surveys, which allow observing the composition of the assemblies of these insects, with the aim of monitoring impacts in natural areas has only recently been realized. The present study focuses on the artificial night lighting as a possible impact on assemblies of bioluminescent beetles. To the knowledge of the fauna of luminous beetles in the State of São Paulo, surveys were conducted by sampling at three sites of the Atlantic Forest in the SA of Paranapiacaba. The species found were: Aspisoma lineatum, Aspisoma physionotum, Aspisoma sp., Cratomorphus beskei, Cratomorphus giganteus, Photinoides penai, Photinus sp1, Photinus sp9, Ethra aff. malledicta ou axilaris, Ethra aff. adicta, Cladodes demoulini, Cladodes flabelicornis, Amydetes sp., Bicellonycha sp., Bicellonycha sp8, Pyrogaster lunifer, Pyrogaster moestus, Pyrogaster sp3 ref. (PORTO, 2011), Photuris elliptica, Photuris sp1, Photuris sp7 Stenophrixotrix sp1, Brasilocerus sp1, Phrixotrix hirtus, Pseudophengodes sp1, Hapsodrilus pyrotis, Pyroptesis cincticollis, Ptesiomopsia luculenta, Pyrearinus candelarius, Pyrearinus micatus e Pyrophorus divergens. The investigated area in SA Paranapiacaba has the second highest species richness of bioluminescent insects of the state of São Paulo until now. From the cluster analysis was done with the data obtained in the field and published data to categorize areas as more and less urbanized was possible to deduce a dependence relationship between species and area in which they can occur. Like other studies, lower richness of bioluminescent beetles in more urbanized areas was observed, we chose a species to investigate the possible effects of artificial lighting. For the study we used the method of counting grid in two similar areas, where only one had artificial lighting. Was possible to compare the data obtained from the two sites with randomization of the same data through a robust non-parametric test, thereby we verified that the sample populations showed no number of different occurrences, the p value is not significant (t=1,780787, R=5000, P=0,059988). We conclude that Bicellonycha lividipennis is not sensitive to ligth of sodium vapor lamps. So this species is not a good indicator species to light pollution for this type of light source. The bioluminescence spectra and the sodium light were superimposed; a possible explanation for that B. lividipennis is not sensitive to light sodium is the activity of the species which is relatively early when there is still strong lighting of twilight.